Implicatures in Altfatah Nando’s Short Movie Terlanjur Mencinta - Nurhamidah, Idha -; Soepriatmadji, Liliek; Purwanto, Sugeng (Lingual Journal of Language and Culture; Vol 12 No 2 (2021): Lingual: Journal of Language and Culture, 2021)
YouTube has been flooded with contents within a movie genre, mostly the products by junior creators. It is therefore important to appreciate their works to maintain their creativities and innovations. Positive responses to such literary works are also required to improve their quality writing. The current study was aimed at identifying and at the same time construing the implicatures found in each act of the movie entitled “Terlanjur Mencinta” directed by Alfatah Nando. George Yule’s pragmatic theory (1996) was used in relation to implicatures caused by conversational maxims (Grice, 1975) supported by linguistic evidence-based contextual interpretation, namely utterances and stage directions.  Findings show that generalized conversational implicatures were identified, namely 12 implicatures in which 42% was due to violation of manner maxim, 33% attributed to that of relation maxim, 17% due to that of quantity maxim, and 8% due to that of quality maxim. In addition, 4 conventional implicatures were found in the monologue. The study concludes that the implicatures can be easily understood through the contexts of situations. It is recommended that future researchers can formulate the ideal proportion and distribution of implicatures in a particular text in terms of quality, employing comparative rhetoric and a special research instrument.